2019
DOI: 10.1101/555128
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constrained inference in sparse coding reproduces contextual effects and predicts laminar neural dynamics

Abstract: A central goal in visual neuroscience is to understand computational mechanisms and to identify neural structures responsible for integrating local visual features into global representations. When probed with complex stimuli that extend beyond their classical receptive field, neurons display non-linear behaviours indicative of such integration processes already in early stages of visual processing. Recently some progress has been made in explaining these effects from first principles by sparse coding models w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…These so called inference populations iteratively perform inference on the potential causes of their inputs from each stochastic spike impinging on the population (Ernst et al, 2007). While the corresponding dynamics might appear artificial, it captures the essence of models with more biologically realistic neurons (Rozell et al, 2008; Moreno-Bote and Drugowitsch, 2015; Zhu and Rozell, 2015) that perform sparse efficient coding, which is a leading hypothesis for understanding coding in the brain (Olshausen and Field, 2006; Spanne and Jörntell, 2015; Zhu and Rozell, 2015; Capparelli et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These so called inference populations iteratively perform inference on the potential causes of their inputs from each stochastic spike impinging on the population (Ernst et al, 2007). While the corresponding dynamics might appear artificial, it captures the essence of models with more biologically realistic neurons (Rozell et al, 2008; Moreno-Bote and Drugowitsch, 2015; Zhu and Rozell, 2015) that perform sparse efficient coding, which is a leading hypothesis for understanding coding in the brain (Olshausen and Field, 2006; Spanne and Jörntell, 2015; Zhu and Rozell, 2015; Capparelli et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…From their extraordinarily long wiring (up to 2-3 mm), LRCs are distinguished from local connections of a short lateral spread (up to 0.5 mm) 2226 (Fig 1c). Previous studies have suggested that LRCs may play a particular role in visual processing, compensating for their large wiring cost, and possibly contributing to layer-wide functions such as contextual modulation at early stages 2729 . However, the exact functions of LRCs for visual processing are still unknown.…”
Section: Introductionmentioning
confidence: 99%